Direct current distribution network protection scheme based on inductive current limiting. Issue 1 (July 2021) - Lv, Jiale; Liu, Jianwen; Wu, Zaijun; Cao, Xiaoyong; Yang, Jinggang
Abstract: Converter blocking in the case of pole-to-pole short circuit of the direct current (DC) distribution network can cause large-scale power outage and slow system recovery. Given this issue, a scheme of short circuit protection between poles of the DC distribution network based on the cooperation of fault current limiting module and DC circuit breaker is proposed in this paper. According to the inductive current limiting topology, the transient characteristics of the bridge arm current and the fault current on the DC side of the converter are analyzed, and the theoretical calculation method and selection principle of the current limiting inductor parameters are given. The proposed protection scheme can realize the fault ride-through of the converter during the pole-to-pole short circuit, reduce the scope of power outage and quickly restore the system. The simulation results under the PSCAD/EMTDC environment verify the correctness and feasibility of the protection scheme.